А.ПАЗЫЛОВ ГҮРРИҢЛЕРИНДЕГИ СЮЖЕТЛИК ӨЗГЕШЕЛИКЛЕР - Ктайбекова, З.К. (FAN va JAMIYAT, 2023)
The article analyzes the features of the plot in the stories. The stories of A. Pazylov were studied as an object of research. The artistic skill of the author in creating the plot in the stories "Tush", "Crying of Tursunboy", "Hazyl" and other stories was analyzed on the basis of examples. The characteristics of the creation of the hero‘s image in the stories, the use of dream motifs, dialogue and other pictorial methods have been analyzed on a scientific-theoretical basis.